« On n’avait pas l’impression de travailler à la mine » - Irène Le Roy Ladurie; Maël Rannou (Comicalités)
A little-known figure in the history of Pif Gadget magazine, Claude Bardavid joined the magazine a few years after its creation, becoming the last editor-in-chief of the original version from 1985 to 1993. In this interview, he looks back at how he joined the editorial staff of the Communist magazine and how his career developed. As a simple editor, he was involved in all aspects of the periodical, working on gadgets, special operations projects, bandes dessinées, and even the launch of a spin-off (Pifou, le journal). A close witness to the life of Pif Gadget up until its end, he provides a real insight into the day-to-day life of a title that was emblematic of French-language children’s culture in the second half of the 20th century, over a long period of major changes.